Structure-based molecular screening and dynamic simulation of phytocompounds targeting VEGFR-2: a novel therapeutic approach for papillary thyroid carcinoma - Wang, Shuai; Zhang, Lingqian; Zhang, Wenjun; Zeng, Xiong; Mei, Jie; Xiao, Weidong; Yang, Lijie (Frontiers in Pharmacology, 2025)
Papillary thyroid carcinoma (PTC) is the most prevalent type of thyroid cancer, with aggressive variants presenting major therapeutic challenges. Vascular endothelial growth factor receptor-2 (VEGFR-2) is a key regulator of tumor angiogenesis and is highly expressed in PTC, making it a promising target for therapeutic intervention. This highlights the potential of VEGFR-2 inhibition as an effective strategy for managing PTC. In this study, we employed virtual drug screening, molecular dynamics simulations, and binding free energy calculations to identify potential VEGFR-2 inhibitors from the African natural product database (AfroDb). Our virtual drug screening identified three lead compounds SA_0090, 17.3.1.7.8 and BMC_0005 with a docking scores of −9.04 kcal/mol, −8.96 kcal/mol, and −8.33 kcal/mol respectively, surpassing the control compound (−8.39 kcal/mol). Molecular dynamics simulation analysis confirmed the dynamic stability, structural compactness, and minimal residual fluctuations of the 17.3.1.7.8 and BMC_0005 compounds-VEGFR2 complexes. The binding free energy calculations further supported the strong interactions, with values recorded as −60.3861 ± 0.39 kcal/mol for the control, −52.2732 ± 0.37 kcal/mol for SA_0090, −52.7797 ± 0.62 kcal/mol for 17.3.1.7.8, and −61.476 ± 0.59 kcal/mol for BMC_0005. Additionally, the selected compounds exhibited highly favorable ADMET properties, including optimal water solubility, efficient gastrointestinal absorption, and a non-hepatotoxic profile, all aligning with Lipinski’s rule of five. In conclusion, these findings highlight 17.3.1.7.8 and BMC_0005 compounds as compelling candidates for VEGFR-2 inhibition, offering a promising therapeutic avenue for papillary thyroid carcinoma, warranting further in vitro and in vivo validation for potential therapeutic use.